2021
DOI: 10.1038/s42003-021-02923-3
|View full text |Cite
|
Sign up to set email alerts
|

IQ-Switch is a QF-based innocuous, silencing-free, and inducible gene switch system in zebrafish

Abstract: Though various transgene expression switches have been adopted in a wide variety of organisms for basic and biomedical research, intrinsic obstacles of those existing systems, including toxicity and silencing, have been limiting their use in vertebrate transgenesis. Here we demonstrate a novel QF-based binary transgene switch (IQ-Switch) that is relatively free of driver toxicity and transgene silencing, and exhibits potent and highly tunable transgene activation by the chemical inducer tebufenozide, a non-tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…To address the flaws of EUI gene switch, we attempted to integrate the binary IQ-Switch, originally optimized for zebrafish transgenesis, 34 with several modifications. To create a novel SIQ, we assembled all the necessary elements for IQ-based transgene toggling into a pENTR-EUI vector.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the flaws of EUI gene switch, we attempted to integrate the binary IQ-Switch, originally optimized for zebrafish transgenesis, 34 with several modifications. To create a novel SIQ, we assembled all the necessary elements for IQ-based transgene toggling into a pENTR-EUI vector.…”
Section: Resultsmentioning
confidence: 99%
“…Since the native QF transcriptional activator was highly toxic in fruit flies and zebrafish, 28 , 29 , 30 , 34 the QF had to be extensively amended before being adopted in animals to eliminate its cellular toxicity. We previously minimized the cytotoxicity issues of QF by removing virulent modules from the middle domain to the C-terminal end of large transactivation domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the common kinase-activating variant in CFC syndrome BRAF Q257R in zebrafish embryos increased the major/minor axis ratio [104]. Also, overexpression of BRAF V600E before gastrulation in zebrafish embryos caused severe embryonic malignancy with truncated posterior structure and compromised forebrain, while later induction led to craniofacial deformities resembling CFC syndrome [105] (Table S2). Activating mutations in MEK1 have different strengths, which are correlated with the severity of the phenotypes observed in human patients affected by these mutations [106].…”
Section: Neuro-phenotypic Complexity In Rasopathies With Insights Fro...mentioning
confidence: 99%
“…In zebrafish embryos, studies have shown that expression of BRAF Q257R increased the major/minor axis ratio, a phenotype that was prevented by treatment with the MEK inhibitors CI-1040 and PD0325901 [104,155]. Similarly, the CFC-syndrome-like phenotypes associated with ectopic expression of BRAF V600E were profoundly ameliorated by simultaneous treatment with vemurafenib [105]. Furthermore, in the zebrafish model of NF1, treatment with sunitinib, a RTK inhibitor, effectively arrested the progression of transplanted MPNSTs, and combination treatment with both sunitinib and trametinib, a MEK inhibitor, enhanced this therapeutic effect [87].…”
Section: Effective Neurological Treatments and Rasopathy Inhibitors U...mentioning
confidence: 99%